Implementing national hospital accreditation standards for patient safety - Familiantoro, Familiantoro; Suryawati, Chriswardani; Raharjo, Mursid (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Patient safety is a crucial aspect in improving the quality of healthcare and reducing the risk of preventable injuries in hospitals. Incident data suggests that the quality of care still needs to be improved for safe and quality care. Purpose: To examine the implementation of the 2022 national hospital accreditation standards for patient safety goals at RSI PKU Muhammadiyah Pekajangan, evaluate the hospital’s efforts in reducing patient safety incidents, and assess patient satisfaction. Method: Qualitative phenomenological approach with in-depth interview techniques and triangulation. Informants consisted of 3 main informants and 5 triangulation informants. Results: Although the hospital has undertaken various initiatives to reduce risks and enhance patient safety, incidents related to patient safety continue to occur. Nevertheless, the implementation of patient safety measures appears to positively influence patient satisfaction. Survey results indicate an increase in patient satisfaction following the promotion of patient safety programs. Additionally, the hospital achieved a 91.67% score in meeting patient safety goals, reflecting substantial compliance with accreditation standards. The adoption of the Hospital Accreditation Standards in accordance with Ministry of Health Regulation No. 1128 of 2022 has also contributed positively to strengthening patient safety practices. Conclusion: Findings from in-depth interviews across the dimensions of structure, process, and outcomes indicate that, following accreditation, RSI PKU Muhammadiyah Pekajangan has consistently implemented the Hospital Accreditation Standards in accordance with Ministry of Health Regulation No. 1128 of 2022. A notable reduction in Near Miss (NM) incidents was observed, along with a high level of patient satisfaction. The achievement of full accreditation and adherence to the updated standards have had a positive impact on enhancing patient safety within the hospital.